Rab18 interacted with V-set and immunoglobulin domain-containing 4 (VSIG4) to involve in the apoptosis of glioma and the sensitivity to temozolomide. Issue 1 (1st January 2021) - Yang, Kai; Wang, Zhi
ABSTRACT: Rab18 and V-set and immunoglobulin domain-containing 4 (VSIG4) were reportedly implicated in the malignant progression of glioma. In this study, their relationship was further explored, accompanied by the investigation into their effects on the sensitivity of temozolomide (TMZ). The proliferation and apoptosis of U87-MG and U251-MG were detected after Rab18 silencing through CCK8 assay and flow cytometry, respectively. The interaction between Rab18 and VSIG4 was predicted through database and verified by immunoprecipitation assay. The suspicion that whether the sensitivity of glioma to temozolomide was affected by the Rab18-VSIG4 interaction was explored through CCK8 assay. We observed decreased proliferation and increased apoptosis and TMZ sensitivity in U87-MG and U251-MG treated by siRNA-Rab18. Not only was the interaction predicted using database, but also it was confirmed by IP assay. Intriguingly, VSIG4 overexpression effectively reversed above biological process and TMZ sensitivity caused by Rab18 silencing. To conclude, the Rab18-VSIG4 interaction was implicated in the proliferation and apoptosis of glioma, as well as TMZ sensitivity. Targeting the interaction between Rab18 and VSIG4 may help exploit new therapies to enhance TMZ sensitivity for treating patients with glioma. Graphical abstract: uf0001